2021
DOI: 10.1001/jamanetworkopen.2020.33769
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Revised US Preventive Services Task Force Lung Cancer Screening Guideline Among Women and Racial/Ethnic Minority Populations

Abstract: IMPORTANCELung cancer incidence and mortality disproportionately affect women and racial/ ethnic minority populations, yet screening guidelines for the past several years were derived from clinical trials of predominantly White men. To reflect current evidence, the US Preventive Services Task Force (USPSTF) has revised the eligibility criteria, which may help to ameliorate sex-and race/ ethnicity-related disparities in lung cancer screening. OBJECTIVE To determine the changes associated with the revised USPSTF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
39
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 17 publications
5
39
0
Order By: Relevance
“…As current guidelines do not adequately identify particular high-risk groups, specifically women and under-represented minorities, the USPSTF published modified guidelines in 2021, liberalising the pack year history to 20 and the lower age limit to 50 years [6]. While the percentage of both men and women eligible for screening will increase with expanded eligibility criteria [49], a rising proportion of the population will continue to be excluded from the screening criteria given the rapidly and constantly changing demographics and epidemiology of lung cancer worldwide. In particular, young women who are still of childbearing age are at increasing risk of being left out of screening guidelines; however, reassuringly, the development of lung cancer during pregnancy is quite rare [50].…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…As current guidelines do not adequately identify particular high-risk groups, specifically women and under-represented minorities, the USPSTF published modified guidelines in 2021, liberalising the pack year history to 20 and the lower age limit to 50 years [6]. While the percentage of both men and women eligible for screening will increase with expanded eligibility criteria [49], a rising proportion of the population will continue to be excluded from the screening criteria given the rapidly and constantly changing demographics and epidemiology of lung cancer worldwide. In particular, young women who are still of childbearing age are at increasing risk of being left out of screening guidelines; however, reassuringly, the development of lung cancer during pregnancy is quite rare [50].…”
Section: Screening and Diagnosismentioning
confidence: 99%
“…In particular, it would be ideal if longitudinal smoking data were available from EHRs through their Health Level 7 (HL7) Fast Healthcare Interoperability Resources (FHIR) application programming interfaces, so that the data can be used by external apps and Web Services connected to the EHR to identify a patient’s eligibility and appropriateness for screening. 19 , 26 …”
Section: Discussionmentioning
confidence: 99%
“…12 Similarly, a crosssectional study using data from the Centers for Disease Control and Prevention's Behavioral Risk Factor Surveillance System survey showed that although the chestjournal.org 2021 USPSTF criteria improve eligibility for LCS for women, Blacks, and Hispanics, LCS "inequities may persist without tailored eligibility criteria." 11 Pinsky and colleagues also found lower LCS E-I ratios for all women, but most notably Asian women, compared with men. This is particularly relevant, because subanalyses of the two largest LCS studies, the National Lung Screening Trial (NLST) and the Dutch-Belgian Randomized Lung Cancer Screening Trial (NELSON), suggest greater mortality benefits for women who receive LCS compared with men.…”
mentioning
confidence: 91%
“…10 The 2021 USPSTF LCS recommendations expand eligibility criteria to include younger individuals with a lower cumulative smoking history to minimize disparities in eligibility. 11 However, as demonstrated by Pinsky and colleagues, 7 disparities persist. A recent study using the 2015 NIHS data found that racial inequities in LCS did not decrease in 2021 vs 2013 USPSTF eligibility criteria.…”
mentioning
confidence: 95%
See 1 more Smart Citation